2021
DOI: 10.14336/ad.2021.0225
|View full text |Cite
|
Sign up to set email alerts
|

Organ-differential Roles of Akt/FoxOs Axis as a Key Metabolic Modulator during Aging

Abstract: FoxOs and their post-translational modification by phosphorylation, acetylation, and methylation can affect epigenetic modifications and promote the expression of downstream target genes. Therefore, they ultimately affect cellular and biological functions during aging or occurrence of age-related diseases including cancer, diabetes, and kidney diseases. As known for its key role in aging, FoxOs play various biological roles in the aging process by regulating reactive oxygen species, lipid accumulation, and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 161 publications
0
5
0
1
Order By: Relevance
“…Insulin promotes glycogen synthesis and inhibits both glycogenolysis and gluconeogenesis via the regulation of multiple pathways downstream of insulin; this includes activation in the liver of PI3K/Akt signaling, inhibition of glycogen synthase kinase 3β (GSK3β) and inhibition of forkhead box protein O1 (Foxo1) [ 46 , 47 ]. Previous studies have revealed that dysregulation of hepatic insulin signaling results in impaired glucose homeostasis and the development of insulin-resistance during aging [ 48 ]. Notably, in the Veh-treated old mice, most of the DEGs related to insulin signaling pathway are significantly increased in the livers; most of these DEGs belong to four major functional groups, namely inhibition of insulin signaling, glucose metabolism, lipid metabolism, and cell proliferation/differentiation (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin promotes glycogen synthesis and inhibits both glycogenolysis and gluconeogenesis via the regulation of multiple pathways downstream of insulin; this includes activation in the liver of PI3K/Akt signaling, inhibition of glycogen synthase kinase 3β (GSK3β) and inhibition of forkhead box protein O1 (Foxo1) [ 46 , 47 ]. Previous studies have revealed that dysregulation of hepatic insulin signaling results in impaired glucose homeostasis and the development of insulin-resistance during aging [ 48 ]. Notably, in the Veh-treated old mice, most of the DEGs related to insulin signaling pathway are significantly increased in the livers; most of these DEGs belong to four major functional groups, namely inhibition of insulin signaling, glucose metabolism, lipid metabolism, and cell proliferation/differentiation (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The calcium signaling pathway is involved in nearly every physiological function of the normal cell cycle, including cell growth, proliferation, and differentiation ( 55 ). As calcium signaling is important for AKI, this process could be manipulated therapeutically to improve AKI ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…In aging, the occurrence of diabetes and obesity is associated with insulin resistance [100], which leads to the downregulation of AKT and upregulation of FOXOs. In addition, AKT demonstrates differential actions in separate organs [101,102].…”
Section: Pi3k/mtor/akt Pathwaymentioning
confidence: 99%